2009
DOI: 10.13031/2013.25422
|View full text |Cite
|
Sign up to set email alerts
|

Selected Additives Did Not Improve Flowability of DDGS in Commercial Systems

Abstract: An experiment was conducted at a commercial, dry-grind ethanol plant to determine if selected additives would improve flowability of dried distillers grains with solubles (DDGS). Main treatment effects were moisture content of DDGS (9 vs. 12% w.b.) and anti-caking agent (ACA). The ACA treatments were: No additive (Control); a moisture migration control agent at 2.5 kg/metric ton (DMX-7); calcium carbonate at 2% w.b. (Calcium carbonate); or a clinoptilolite zeolite at 1.25% w.b. (Zeolite). The ACA were added at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Replicate (summer or fall) was included as a random effect. Previous research reported from our laboratory indicated that flowability of feed was reduced substantially once moisture content exceeded 10% (Johnston et al, 2009) and feed is hygroscopic and can absorb water from the surrounding environment. Thus, moisture content of the feed corresponding with the day of feed flow determinations was used as a covariate in all statistical analyses.…”
Section: Statistical Analysis For Experimentsmentioning
confidence: 88%
See 4 more Smart Citations
“…Replicate (summer or fall) was included as a random effect. Previous research reported from our laboratory indicated that flowability of feed was reduced substantially once moisture content exceeded 10% (Johnston et al, 2009) and feed is hygroscopic and can absorb water from the surrounding environment. Thus, moisture content of the feed corresponding with the day of feed flow determinations was used as a covariate in all statistical analyses.…”
Section: Statistical Analysis For Experimentsmentioning
confidence: 88%
“…The number of taps required to establish feed flow was recorded. In addition, a subjective flowability score (1 = free flowing, 10 = completely bridged) was assigned to the feed flow as described by Johnston et al (2009). Tapping and subjective flowability scores were performed by the same individual throughout the trial.…”
Section: Measurements and Calculations In Experimentsmentioning
confidence: 99%
See 3 more Smart Citations